Intended college enrollment and educational inequality: Do students lack information? - Frauke H. Peter; Vaishali Zambre (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Despite increasing access to university education, students from disadvantaged or non-academic family backgrounds are still underrepresented at universities. In this regard, the economic literature mainly studies the effect of financial constraints on post-secondary educational decisions. Our knowledge on potential effects of other constraints regarding university education is more limited. We investigate the causal relationship between information and educational expectations using data from a German randomized controlled trial in which students in high schools were treated with information on the benefits as well as on different funding possibilities for university education. We find that the provision of information increases intended college enrollment for students from a non-academic family background, while it leads students from academic backgrounds to lower their enrollment intentions. Our results suggest that educational inequality can be reduced by providing students with relevant information, while simultaneously improving post-secondary education matches.
Keywords: I21; I24; J24; 330; Randomized Controlled Trial; Information Deficit; Educational Expectation; College Enrollment; Educational Inequality